1976
DOI: 10.1159/000144580
|View full text |Cite
|
Sign up to set email alerts
|

Effect of testosterone propionate on the ultrastructure of the preputial gland in the rat

Abstract: Testosterone propionate accelerates the maturation of acinar cells in the preputial gland of female rats. The weight of the preputial gland was increased significantly and the gland contained a large amount of secretory material. Various stages of maturation of acinar cells were observed. In an early stage, cells contained predominantly rough endoplasmic reticulum. In a second stage, lipid accumulated in association with focal areas of smooth endoplasmic reticulum. Membrane-bound dense bodies similar to lysoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Although hexadecanoic acid and cholesterol were also richer in males than in females, the former does not attract females ( Gawienowski et al 1975 ) and the latter has never been reported as an animal pheromone compound ( Wyatt 2003 ). Additionally, our results about the testis and ovary dependency of rat preputial gland were consistent with previous work in a sense that both androgen and estrogen can hypertrophy preputial glands in the rat (Marois M and Marois G 1974; Nickerson et al 1976 ; Lucas et al 1982 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although hexadecanoic acid and cholesterol were also richer in males than in females, the former does not attract females ( Gawienowski et al 1975 ) and the latter has never been reported as an animal pheromone compound ( Wyatt 2003 ). Additionally, our results about the testis and ovary dependency of rat preputial gland were consistent with previous work in a sense that both androgen and estrogen can hypertrophy preputial glands in the rat (Marois M and Marois G 1974; Nickerson et al 1976 ; Lucas et al 1982 ).…”
Section: Discussionsupporting
confidence: 92%
“…Their excretions are discharged into the voided urine to communicate information about species, sex, and dominance status to conspecifics ( Brinck and Hoffmeyer 1984 ; Brown 1985 ; Welsh et al 1988 ; Harvey et al 1989 ; Novotny et al 1990 ; Novotny, Ma, et al 1999). Under androgenic control, rodent preputial glands are often larger in males but smaller or absent in females ( Nickerson et al 1976 ; Gawienowski 1977 ; Brown 1985 ; Zhang, Rao, et al 2007; Zhang, Zhao, et al 2007). However, in some rat species (e.g., Rattus rattus , Rattus losea , Rattus nitidus , Niviventer confucianus , Niviventer fulvescens , and Leopoldamys edwardsi ), they are like sized between the sexes ( Brown 1985 ; Mallick 1991 ; Zhang J-X, Xiao Z-S, Liu X-H, Cong L, unpublished observation).…”
Section: Introductionmentioning
confidence: 99%
“…The structure and pheromonal activity of the glands are regulated by both pituitary and sex hormones, including testosterone, estrogen, and progesterone (Pietras, 1981;Ebling, 1977;Nickerson et al, 1976). An increased incidence of preputial and clitoral gland neoplasms has been associated with the administration of a number of chemicals.…”
Section: Carcinogenicitymentioning
confidence: 99%
“…Androgen administration produces notable changes in female preputial glands as well. In females, androgens induce glandular hypertrophy (Korenchevski et al, 1937;Burdick and Gamon, 1941;Mugford and Nowell, 1971b;and Nickerson et al, 1976), stimulate the formation of a thick, white secretory product (Korenchevski et al, 1937), and increase the amount of secretion (Nickerson et al, 1975). Glandular enlargement in immature female rats was described by Salmon (1938) as early as 48 hours after the first TP injection.…”
Section: Preputial Glandsmentioning
confidence: 99%
“…Normal adult female glands vary from 10-16 mg, but after TP injection they increase in weight to a range of 35 to 38 mg, and ovariectomized glands also enlarge. In female rats testosterone propionate hastens the maturation of preputial gland acinar cells and produces changes in morphology which consists of acinar cells all having a similar stage of development, rather than many different stages of de velopment as seen in male rats (Nickerson et al, 1976).…”
Section: Preputial Glandsmentioning
confidence: 99%